Dream's e-Brochure / Muhammad Nufail Akram Mat Nasir ... [et al.] - Mat Nasir, Muhammad Nufail Akram; Mohd Rosli, Farah; Mohd Zahid, Siti Zarifah Nasuha; Munira, Nur Izwanina Munira (2022)
This product has been innovated according to acceptable standards and facilitates the public. This product will be one of the new products of this century. This is not only in line with the current Covid-19 era but can even help those who love to seek information. Information is very important for the convenience of the public. With a wide range of interesting information and attractions, it will be the choice of many people. this will advance the existing business. with the internet and gadgets, we can find information at our fingertips.